2003
DOI: 10.1029/2002ja009812
|View full text |Cite
|
Sign up to set email alerts
|

On the nature of three‐dimensional magnetic reconnection

Abstract: [1] Three-dimensional magnetohydrodynamic reconnection in a finite diffusion region is completely different in many respects from two-dimensional reconnection at an X-point. In two dimensions a magnetic flux velocity can always be defined: two flux tubes can break at a single point and rejoin to form two new flux tubes. In three dimensions we demonstrate that a flux tube velocity does not generally exist. The magnetic field lines continually change their connections throughout the diffusion region rather than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
131
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(132 citation statements)
references
References 13 publications
1
131
0
Order By: Relevance
“…The presence of a current sheet at the null, together with a parallel electric field, is a strong indication that reconnection is taking place in the vicinity of the null (we actually expect that field lines change their connectivity everywhere within the volume defined by the current sheet (the 'diffusion region'), not only at the null itself 21,32 , which is special only in that the footpoint mapping is discontinuous there). It can be shown 32 that Ψ = x=y=0 E dz provides a measure of the reconnection rate at the null.…”
Section: Parallel Electric Field and Reconnectionmentioning
confidence: 99%
“…The presence of a current sheet at the null, together with a parallel electric field, is a strong indication that reconnection is taking place in the vicinity of the null (we actually expect that field lines change their connectivity everywhere within the volume defined by the current sheet (the 'diffusion region'), not only at the null itself 21,32 , which is special only in that the footpoint mapping is discontinuous there). It can be shown 32 that Ψ = x=y=0 E dz provides a measure of the reconnection rate at the null.…”
Section: Parallel Electric Field and Reconnectionmentioning
confidence: 99%
“…The real magnetic topologies are even more complex than the magnetic fields predicted by the linear force free state, but for the statistical analysis presented in their article the linear force free extrapolation is probably suitable. Using simple criteria for the potentially unstable currents, e.g the angular difference between two adjacent magnetic field vectors, B 1 and B 2 to exceed a certain value, since the steep magnetic field gradients favor magnetic reconnection in 3D magnetic topologies [28], they were able to define the location of the UCS. They concluded that AR form naturally UCS even during their formation stage (Fig.…”
Section: Energy Release and Particle Acceleration In Complex Magneticmentioning
confidence: 99%
“…Such models are useful in obtaining the magnetic energy conversion (or reconnection) rates (Parker 1963), as well as providing the geometrical characteristics of the current layer (Priest & Raadu 1975;Tur & Priest 1976). However, in the works of Green & Sweet (1967) and Petschek & Thorne (1967), the authors had to modify the original Petschek reconnection scenario (e.g.…”
Section: Current Layer Formation and Evolutionmentioning
confidence: 99%
“…Syrovatskii 1966;Priest & Raadu 1975). Then, the consequences of magnetic reconnection in those singular regions were investigated analytically in more detail, although the first attempts mainly treated the problem as a boundary layer associated with some singular structure in a nearly ideal plasma (e.g.…”
Section: Magnetic Topology Of Solar Flaresmentioning
confidence: 99%